Ameliorating antipsychotic-induced weight gain by betahistine: Mechanisms and clinical implications. (April 2016) - Lian, Jiamei; Huang, Xu-Feng; Pai, Nagesh; Deng, Chao
Graphical abstract: Highlights: Betahistine co-treatment ameliorates olanzapine-induced weight gain through hypothalamic H1 R AMPKα, NPY pathways. Betahistine co-treatment reduces olanzapine-induced dyslipidaemia via AMPKα-SREBP-1-PPARα-dependent pathway in the liver. Co-treatment with betahistine does not affect the therapeutic efficacy of antipsychotics. Abstract: Second generation antipsychotic drugs (SGAs) cause substantial body weight gain/obesity and other metabolic side-effects such as dyslipidaemia. Their antagonistic affinity to the histaminergic H1 receptor (H1 R) has been identified as one of the main contributors to weight gain/obesity side-effects. The effects and mechanisms of betahistine (a histaminergic H1 R agonist and H3 receptor antagonist) have been investigated for ameliorating SGA-induced weight gain/obesity in both animal models and clinical trials. It has been demonstrated that co-treatment with betahistine is effective in reducing weight gain, associated with olanzapine in drug-naïve patients with schizophrenia, as well as in the animal models of both drug-naïve rats and rats with chronic, repeated exposure to olanzapine. Betahistine co-treatment can reduce food intake and increase the effect of thermogenesis in brown adipose tissue by modulating hypothalamic H1 R-NPY-AMPKα (NPY: neuropeptide Y; AMPKα: AMP-activated protein kinase α) pathways, and ameliorate olanzapine-induced dyslipidaemia through modulation of AMPKα-SREBP-1-PPARα-dependent pathways (SREBP-1: Sterol regulatory element binding protein 1; PPARα: Peroxisome proliferator-activated receptor-α) in the liver. Although reduced locomotor activity was observed from antipsychotic treatment in rats, betahistine did not affect locomotor activity. Importantly, betahistine co-treatment did not influence the effects of antipsychotics on serotonergic receptors in the key brain regions for antipsychotic therapeutic efficacy. However, betahistine co-treatment reverses the upregulated dopamine D2 binding caused by chronic olanzapine administration, which may be beneficial in reducing D2 supersensitivity often observed in chronic antipsychotic treatment. Therefore, these results provide solid evidence supporting further clinical trials in treating antipsychotics-induced weight gain using betahistine in patients with schizophrenia and other mental disorders.